Evaluation of left atrial function in asymptomatic dogs with chronic myxomatous mitral valve disease: two-dimensional feature-tracking echocardiography and Simpson’s monoplanar methods - Coelho,Mariana R. (2020)
ABSTRACT: The present study evaluated the volume and function of the left atrium by two-dimensional echocardiographic feature-tracking imaging (2D-FTI) and Simpson’s monoplanar modeling in dogs with asymptomatic degenerative mitral valve disease (DMVD). The study consisted of 80 dogs that were divided into the following three groups: Group 1, 21 dogs (A); Group 2, 30 dogs (B1) and Group 3, 29 dogs (B2). The variable strain (contraction phase) was significantly lower in Group 3 than in Group 1 (12.92±4.54 x 16.69±5.74, p=0.014), and significant differences in the contraction strain index (CSI) were observed between all of the groups that were evaluated (1 = 46.82±8.10, 2 = 39.88±8.03, 3 = 35.25±5.64, p<0.0001). The atrial diastolic volume index (AdVi) that was measured by 2D-FTI was significantly higher in Group 3 than in Group 1 (1.31±0.95 x 0.96±0.31, p=0.038), and the atrial cardiac index (ACI) was also higher in Group 3 than in Group 1 (102.38±80.18 x 78.19±33.38, p=0.030). Atrial function was assessed by Simpson’s monoplanar method, which demonstrated an increase in the left atrial systolic volume, while the contractile function decreased with an increasing disease severity (Group 1 0.21±0.06; Group 2 0.25±0.06; Group 3 0.32±0.08, p<0.0001). The intraobserver and interobserver assessments showed low to moderate variability; most of the values for the coefficient of variation for the variables that were analysed with each method were below 25%. Thus, DMVD was determined to cause an alteration in atrial function, especially in the contraction phase, and even in asymptomatic animals, and the methods of 2D-FTI echocardiography and Simpson’s monoplanar evaluation are sensitive and early methods for the detection of left atrial dysfunction.